Enhancing Students' Cognitive Learning Outcomes through the Implementation of the Discovery-Based Learning Model in Indonesian Language Instruction - Astawa, Made Candrika Widya (Jurnal Penelitian Mahasiswa Indonesia, 2024)
The objective of this classroom action research is to determine the improvement in students' cognitive learning outcomes by using the Discovery Learning model in the Indonesian language curriculum for Grade 3 at SD 3 Kalianget during the 2020/2021 academic year. This group activity research employs both quantitative and qualitative methods. The study was conducted at SD 3 Kalianget with a sample size of 15 students. The classroom action research was carried out in three cycles. Data for this study were collected through online tests using Google Forms, observations, journals, and documents. The results indicated that the percentage of classical completeness and the average student scores in the first session of the first cycle were 46.67% and 66.67, respectively. The percentage of classical completeness and the average student scores in Cycles I and II were 66.67% and 71.67, respectively. The classical completeness rate and average student scores in Session I of Cycle II were between 60-70. The classical completeness rate and average student scores in Session II of Cycle II were between 73.33-76.67. The percentage of classical completeness and average student scores in the first session of Cycle III were 80% and 81.67, respectively. The percentage of classical completeness and the average student scores in the second session of Cycle III were 93.33% and 91.67, respectively